2007
DOI: 10.1038/sj.ejcn.1602628
|View full text |Cite
|
Sign up to set email alerts
|

Selenium status in Southern Tasmania

Abstract: Objective: To assess the selenium status of Southern Tasmanians. Design: Cross-sectional. Settings: One thousand and five hundred adults randomly selected from the electoral roll living in the Greater Hobart region of Southern Tasmania, Australia, were invited to participate. Subjects: The overall response rate was 22% (335/1500). Interventions: A venous blood sample was collected and a questionnaire administered (consisting of brief demographic details and health questions) to subjects who granted informed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…The mean serum Se concentration was similar to the earlier published Tasmanian data of McGlashan et al ( 22 ) of 80·5 μg/l from 171 female blood donors, while a much smaller sample of blood donors in the study of Daniels ( 24 ) had a mean serum Se concentration of 77·4 μg/l ( n 25). Conversely, the most recent southern Tasmanian study of Jacobson et al ( 23 ) has reported a considerably higher mean plasma Se concentration of 109·8 μg/l. Although different sample types (plasma v .…”
Section: Discussionmentioning
confidence: 85%
“…The mean serum Se concentration was similar to the earlier published Tasmanian data of McGlashan et al ( 22 ) of 80·5 μg/l from 171 female blood donors, while a much smaller sample of blood donors in the study of Daniels ( 24 ) had a mean serum Se concentration of 77·4 μg/l ( n 25). Conversely, the most recent southern Tasmanian study of Jacobson et al ( 23 ) has reported a considerably higher mean plasma Se concentration of 109·8 μg/l. Although different sample types (plasma v .…”
Section: Discussionmentioning
confidence: 85%
“…5 They also determined that selenium levels lower than 0.7 µmol/L were associated with more complications and greater mortality. This was considerably lower than previously reported levels for Australia, [164][165][166][167][168][169][170] ( Table 3-2) with the majority of patients having a level below the minimum level of 1.14 -1.27 µmol/L required for maximal GPx activity. 171,173 An additional finding from our study was that cellular components i.e.…”
Section: 128contrasting
confidence: 48%
“…There are also considerable differences across the various regions and states of Australia [164][165][166][167][168][169][170] ( Table 3-2). These variations are largely due to variations in soil selenium levels and ultimately the availability of selenium in foods.…”
Section: Chapter 8 : General Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Commonwealth Electoral Act 1918 and Privacy Act 1988 govern access to use and disclosure of electoral roll data and medical researchers may obtain electoral data for approved research. AEC records have been used successfully to recruit controls for case control studies 2–4 and to recruit participants in population cross‐sectional studies, 5–8 however, generally such studies seek only to recruit individuals of specific gender and/or age group. These results show how AEC records may be employed for recruitment and effective targeting of households with specific exposures or demographics, through the use of an advance letter.…”
Section: Discussionmentioning
confidence: 99%